Physical properties of gelatin extracted from skin of Thai panga fish (Pangasius bocourti Sauvage) - Prommajak, Trakul; Raviyan, Patcharin (Food and Applied Bioscience Journal, 2017)
Gelatin from the skin of Thai panga fish (Pangasius bocourti Sauvage) was pretreated with a solution of 0.8 M sodium chloride and 0.1 M sodium hydroxide and extracted by acetic acid solution pH 4.55 at 55°C for 1 h. Physical properties of the obtained fish gelatin and the commercial bovine bone gelatin were compared. The gel strength (513.75 g), viscosity (3.88 cP), turbidity (73.21%), foaming properties (foam formation ability 1.13 and foam stability 0.71), emulsion stability (34.2 to 44.6%) and adhesiveness (-369.1 g.sec) of the fish skin gelatin were higher, but color (L* 43.62, C* 3.66 and h° 45.28), cohesiveness (0.838) and gel elasticity were lower than those of the bovine bone gelatin. Gelling and melting points of the fish skin gelatin (16.40°C and 26.87°C, respectively) were lower than those of the bovine bone gelatin (18.45°C and 29.90°C, respectively). Results obtained suggest that the gelatin extracted from the skin of Thai panga fish was a potential raw material for producing a gelatin film or use as foaming agent, emulsifying agent or thickener, but not suitable for use as gelling agent.